Entrance to the Garbhagriha of the Suhaveshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The details of the entrance to the garbhagriha (sanctum sanctorum) of the Suhaveshwar Temple can be seen here. The entrance is defined by an ornate dvarashakha (architrave). The pilasters flanking the entrance opening and the vertical and horizontal members of the dvarashakha are all plain. The stone has been painted at some point. The lintel has an icon of Lakulisa. The seated image is two-handed, holding a staff in its left hand. It is shown nude. The presence of this sculpture on the lintel indicates that the temple was affiliated with the Pashupata tradition.